STUDYING THE PREVALENCE EXTENT OF ACNE VULGARIS AMONG SECONDARY AND UNIVERSITY STUDENTS IN KIRKUK CITY - Sohaib Sabah Kasim; Ahmed Abdulrahman; Iman Tajer Abdullah (Scholar Express Journals, 2022)
Acne vulgaris is considered as one of the most important chronic inflammatory disorders of pilosebaceous follicles affects approximately 90% of teenagers. Acne is commonly appeared at puberty age, but in some cases might continue beyond youth till the age of 40's. The reason of this condition is the overproduction of sebum resulted from disturbance of sebaceous glands which increases the chance of developing acne. The current study aims to study the occurrence of acne in secondary school and university students aged (12-24) years from both genders. One hundred and fifty-five skin swabs were collected from both genders in the period from April to May of 2021. The results showed that the females were more vulnerable to acne infection 88(56.8%) in compared to males 67(43.2%). The highest infection percentage was seen in the age group (12-18 years) 88(56.8%), whilst the infection rate among university students (18-24 years) age group was 67(43.2%). Bacteriological study showed that the predominant bacteria present on the skin infection was Propionibacterium acnes 79(51%) followed by Staphylococcus epidermidis 42(27.1%) and Staphylococcus aureus 29(18.7%). The other bacterial isolates were Pseudomonas aeruginosa 3(1.9%) and Klebsiella oxytoca 2(1.3%).
Keywords: Acne Vulgaris; Skin Infection; Teenager Infection